The Relationship Between Body Shaming And Anxiety In Adolescents At Alhusna High School In 2024 - Dwi Agung Riyanto; Fifi Musfirowati; Rina Sumartini (Publikasi Indonesia, 2025)
Body shaming is an unpleasant experience that a person feels when their body shape is viewed negatively by others, which can cause anxiety in individuals, especially teenagers. This study aims to determine the relationship between body shaming treatment and anxiety in adolescents, where the design of this study is correlated with the Cross Sectional Study approach. The sample amounted to 52 respondents, sampling using the total sampling method. The measuring tool used is a questionnaire with the Chi Square statistical test. The results of the study found that there was a relationship between body shaming treatment and adolescent anxiety with a value (p-value of 0.014). It is hoped that the school can collaborate with health centers or health education institutions to provide health education about body shaming by increasing adolescents' knowledge about body shaming and its impact on adolescents.